The Cost of the COVID-19 Crisis: Lockdowns, Macroeconomic Expectations, and Consumer Spending - Olivier Coibion; Yuriy Gorodnichenko; Michael Weber; Michael Weber (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study how the differential timing of local lockdowns due to COVID-19 causally affects households' spending and macroeconomic expectations at the local level using several waves of a customized survey with more than 10,000 respondents. About 50% of survey participants report income and wealth losses due to the corona virus, with the average losses being 5,293 and 33,482 respectively. Aggregate consumer spending dropped by 31 log percentage points with the largest drops in travel and clothing. We find that households living in counties that went into lockdown earlier expect the unemployment rate over the next twelve months to be 13 percentage points higher and continue to expect higher unemployment at horizons of three to five years. They also expect lower future inflation, report higher uncertainty, expect lower mortgage rates for up to 10 years, and have moved out of foreign stocks into liquid forms of savings. The imposition of lockdowns can account for much of the decline in employment in recent months as well as declines in consumer spending. While lockdowns have pronounced effects on local economic conditions and households' expectations, they have little impact on approval ratings of Congress, the Fed, or the Treasury but lead to declines in the approval of the President.
Keywords: E31; C83; D84; J26; 330; subjective expectations; consumer spending; labor market; employment; COVID-19; surveys